2016
DOI: 10.5530/ijmedph.2016.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome: Clinical profile and Consensus to revise Hughes grade 5

Abstract: Background: Guillain-Barré Syndrome (GBS) is an acute, immune-mediated polyradiculoneuropathy and an important cause of acute flaccid paralysis (AFP) worldwide. Respiratory insufficiency requiring ventilator occurs in 30% of patients that prolong the hospital stay, leading to morbidity and mortality. There had been relatively few studies of Guillain-Barre syndrome in adults from South India. Aim: To evaluate clinical profile, epidemiological, laboratory, and electro diagnostic features of patients with GBS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…11,12,15,16 In our study majority >90% patients were treated with Plasmapharesis while in majority of the previous studies 11,12,14,15,17 >90% patients with GBS treated with IVIg. In our study complete recovery were observed in about 56% patients while in other studies 11,12,14,17 >70% patients with GBS were recovered completely. Early arrival (<1 week) to hospital, initiation of treatment in form of plasmapharesis or IVIg and intensive care helped to achieve complete recovery in our study.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…11,12,15,16 In our study majority >90% patients were treated with Plasmapharesis while in majority of the previous studies 11,12,14,15,17 >90% patients with GBS treated with IVIg. In our study complete recovery were observed in about 56% patients while in other studies 11,12,14,17 >70% patients with GBS were recovered completely. Early arrival (<1 week) to hospital, initiation of treatment in form of plasmapharesis or IVIg and intensive care helped to achieve complete recovery in our study.…”
Section: Discussionmentioning
confidence: 49%
“…The mean age was 34 years. Sex ratio showed a slight male preponderance in most of the studies [11][12][13][14][15][16][17] Preceding events prior to the illness in present study is observed in forty two patients (53%) had preceding illness. (Table 1) In most of previous studies shows antecedent event in >50% patients.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations